Enhancing Post-Fire Performance of Lightweight RC Slabs Using Expanded Polystyrene and Steel Fibers: An Experimental Study - Abd, Alaa A.; Abbas, Rafaa M. (Salehan Institute of Higher Education, 2025)
Aggregate significantly influences the mechanical properties of concrete material and has a crucial role in post-fire behavior. This research focuses on investigating the post-fire behavior of a fiber-reinforced one-way slab made from lightweight expanded polystyrene (EPS) aggregate concrete. The experimental study consisted of testing fourteen fiber-reinforced self-compacting concrete (SCC) one-way slabs with EPS as a partial replacement of coarse aggregate. All specimens have identical dimensions of 1800×500×125 mm. The main parameters investigated included fire exposure, EPS replacement ratio, and steel fiber content. The tested specimens were divided into two groups. The first group included seven specimens tested under monotonic static load, whereas the seven specimens of the second group were tested under monotonic static load after being exposed to a steady-state temperature of 700°C for one hour. Following exposure to fire, results revealed a dramatic decrease in the structural performance of the slab specimens, including cracking load, ultimate load, stiffness, absorbed energy, and ductility, especially for the non-fibrous lightweight samples. However, adding EPS beads in the concrete mixture helps in reducing strength degradation due to fire exposure, and the higher the EPS content, the less strength degradation. This result exposed the positive impact of EPS on the structural performance of RC lightweight slabs exposed to fire due to their thermal properties. Moreover, results revealed a significant enhancement in post-fire stiffness, ductility, and absorbed energy of the RC slab due to steel fiber inclusion, showing their constructive impact on the slab performance.